The "Eastern Partnership" Project: Does Poland's Voice the Notion of Refugee. Definition and Distinctions - Carmen Moldovan (CES Working Papers, 2016)
Europe has been recently shaken by the great number of persons coming from Syria and neighbouring countries which were calling themselves “refugees”. According to the United Nations Refugee Agency, since 2015 more than 1 million refugees travelled to Greece. This paper aims to analyze the notion of “refugees” in light of international legal instruments applicable and to draw up distinctions between different categories of migrant persons and those who are really refugees and may apply for international protection under the 1951 UN Convention on refugees. The distinction regarding the use of terms is relevant for shaping the legal status of different persons who leave their country of origin.
Keywords: A1; A2; 330; refugees; international protection; safeguards; limits